OFR-17-73 Assessment Of Electromagnetic Noise Measurements Taken By Bureau Of Mines Contractors ? I. Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1972)
As part of its research and development activities concerning coal mine operational/emergency communications sys terns, the Bureau of Mines commissioned several contractors to conduct electromagnetic (EM) noise studies and measurements that would aid the development of improved coal mine operational/emergency communications systems. The bulk of the noise studies and measurements were conducted in 1971. The Pittsburgh Mining and Safety Research Center (PMSRC) inherited the responsibility for monitoring the electromagnetic noise activities by mid-to-late 1971, and initiated a review and evaluation of the current and planned electromagnetic noise work. Arthur D. Little, Inc., (ADL) was asked by PMSRC to assist it in performing this review and evaluation by placing stronger emphasis on certain tasks of existing Contract No. H0122026. This technical memorandum report presents the findings, conclusions, and recommendations of our review and evaluation of the electromagnetic noise measurements of the five contractors we were asked to examine. Our review and evaluation effort included meetings and telephone discussions with technical staff of each contractor; serving as Technical Discussion Leader of a "Contractor's Round Table Meeting on EM Noise, Surface and Subsurface, Operating and Non-Operating Mines" called by the Bureau of Mines; examination and discussion of contractor reports and relevant open literature; sample verification calculations; and the documentation of our findings, conclusions, and recommendations by this report.